The buffer capacity of airway epithelial secretions - Kim, Dusik; Liao, Jie; Hanrahan, John W. (Frontiers in Physiology, 2014)
The pH of airway epithelial secretions influences bacterial killing and mucus properties and is reduced by acidic pollutants, gastric reflux, and respiratory diseases such as cystic fibrosis (CF). The effect of acute acid loads depends on buffer capacity, however the buffering of airway secretions has not been well characterized. In this work we develop a method for titrating micro-scale (30 µl) volumes and use it to study fluid secreted by the human airway epithelial cell line Calu-3, a widely used model for submucosal gland serous cells. Microtitration curves revealed that HCO3- is the major buffer. Peak buffer capacity (β) increased from 17 to 28 mM/pH during forskolin stimulation, and was reduced by >50% in fluid secreted by cystic fibrosis transmembrane conductance regulator (CFTR)-deficient Calu-3 monolayers, confirming an important role of CFTR in HCO3- secretion. Back-titration with NaOH revealed non-volatile buffer capacity due to proteins synthesized and released by the epithelial cells. Lysozyme and mucin concentrations were too low to buffer Calu-3 fluid significantly, however model titrations of porcine gastric mucins at concentrations near the sol-gel transition suggest that mucins may contribute to the buffer capacity of ASL in vivo. We conclude that CFTR-dependent HCO3- secretion and epithelially-derived proteins are the predominant buffers in Calu-3 secretions.